The Development and Validation Tools of a Caring Dimension Inventory for Measuring Caring in Indonesia - Karo, Mestiana Br (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Introduction: Nursing is a human science of persons and human health-illness experiences that are mediated by professional, personal, scientific, aesthetic, and ethical human care transactions.  Caring  is one of the most important aspects of nursing. Caring is much more than the performance of tasks; caring is a trans personal relationship that the nurse enters into with the patient. The Caring Dimensions Inventory (CDI) is a quantitative tool to measure caring. The conceptual theoretical basis for the tool was guided by an empirical rather than theoretical approach to caring that acknowledges some of the general caring theory literature. The theoretical approaches used were those that supported the operationalization of caring through specific taxonomies and measurements.Objectives :  The purpose of this study was to systematically review to provide a coherent description of relationships, conditions, and practices that foster a caring in the environment, experience from the patients and to describe the caring behaviors of nurses who practice.Methods: Research-ers have conducted systematic integrated literature reviews to effectively retrieve and integrate existing information and provide directions for their research. This study used a systematic literature review. It is a method to “recover, sort and analyze the literatures from [peer-reviewed journals] comprehensively and reproducible by peers” and this process was adopted from the guidelines proposed by utilizing multiple database of literatures published from refereed journals were recovered databases Google Scholar and ProQuest, that seemed in the period of 2011 to 2016.  From the key search words using Caring, Nursing, Patient, Practice. These keywords were chosen because we aimed to identify essential components of currently existing systematic integrated literature reviews in nursing.Results : This systemtic shows same experiences in caring measurements. Six caring measurement tools were presented in the systematic review, with suggestions that the validity, reliability and comparability of available tools remain to be established. This tool was developed by Lea and Watson, (6) it consists of 25 core items of nursing practice to be caring. The items were categorized into the following 3 subscales. Such as psychosocial aspects of care which includes 12 items, technical aspects of care which includes 7 items to be caring, professional aspects of care which includes 6 items to be caring.  Conclusion: This systematic review identified the usage of the Caring Dimension Iventory (and the Nusing Dimension Iventory) are tools that can  produce data and  provide indicators that are valuable in the growth of person-centred practice like nurses’ perceptions of caring, patient in care, getting to know the patient’ and the incongruence between nurses’ and patients’ perceptions of caring.